2004
DOI: 10.1534/genetics.103.026096
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Expression of Maize Phytochrome Family HomeologsSequence data from this article have been deposited with the EMBL/GenBank Data Libraries under accession nos. AY234825, AY234826, AY234827, AY234828, AY234829, AY234830.

Abstract: To begin the study of phytochrome signaling in maize, we have cloned and characterized the phytochrome gene family from the inbred B73. Through DNA gel blot analysis of maize genomic DNA and BAC library screens, we show that the PhyA, PhyB, and PhyC genes are each duplicated once in the genome of maize. Each gene pair was positioned to homeologous regions of the genome using recombinant inbred mapping populations. These results strongly suggest that the duplication of the phytochrome gene family in maize arose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 87 publications
2
63
0
1
Order By: Relevance
“…We have found that Ki-67 score has a significantly positive relationship with total COX-2 expression. Study by Sheehan et al (2004) which is consistent with our finding demonstrated that COX-2 expression may contribute to colonic tumourigenesis by promoting cell growth, new vessel formation, invasiveness and, in particular, metastatic potential. Ki-67 also has positive linear relationship with ß-catenin expression.…”
Section: Discussionsupporting
confidence: 92%
“…We have found that Ki-67 score has a significantly positive relationship with total COX-2 expression. Study by Sheehan et al (2004) which is consistent with our finding demonstrated that COX-2 expression may contribute to colonic tumourigenesis by promoting cell growth, new vessel formation, invasiveness and, in particular, metastatic potential. Ki-67 also has positive linear relationship with ß-catenin expression.…”
Section: Discussionsupporting
confidence: 92%
“…Radiolabeled Ds6-like and R1 gene probes were generated and purified as described (Sheehan et al 2004). Hybridizations were performed as described (Church and Gilbert 1984) at 65°in a bottle incubator (Thermo Hybaid, Needham Heights, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Phytochromes in rice (Oryza sativa) are present as single-copy genes . However, in maize (Zea mays), due to the gene duplication from the ancient tetraploidization in the maize ancestral lineage, phytochrome genes are present as homolog pairs for each of the three genes, known as phyA1 and phyA2, phyB1 and phyB2, and phyC1 and phyC2 (Sheehan et al, 2004). Sharing three classes of phytochromes (phyA/B/C) and missing two counterparts (phyD/E) in monocots suggest unique roles of phyD/E in dicots and also highlight the fundamental differences between the monocot and dicot phytochrome signaling pathways.…”
Section: The Phytochrome-pif Signaling Module Is Evolutionarily Consementioning
confidence: 99%